Be seeded or not be seeded? A study with Olympic judo athletes - Guilheiro, L. M.; Franchini, E. (Journal of Exercise Rehabilitation, 2017)
The main purpose of the present study was to calculate the probability—based on a Bayesian approach—to win a medal in the Olympic Games given the athlete is seeded and to verify if the number one ranked athlete has any advantage compared to other seeded athletes concerning his/her chances to be Olympic champion. For this, data from athletes who took part in the London 2012 and Rio 2016 Olympic Games were considered. For males the probability of seeded athletes to win a medal was 41.1% and 42.9%, while for females it was 35.7% and 44.6% at London 2012 and Rio 2016, respectively. Furthermore, the probability of athletes ranked as number one to become Olympic champion among the seeded athletes was 19.5% and 36.8% for males and 32.3% and 36.8% for females in London 2012 and Rio 2016, respectively. Based on these results the cost-benefit of investing human and financial resources to qualify an athletes among the top eight competitors and his/her exposure to competitions—resulting in technical-tactical analysis of the opponent and higher risk of injury—should be carefully analyzed when determining the competition calendar to each athlete.